Antropização urbana frente aos elementos de cura de mulheres benzedeiras de Castanhal-Pará - SILVA, Gleibson do Nascimento (Universidade Federal do Pará, 2021)
This research assumed the purpose of investigating how women healers are affected in their practices with elements of healing in the city of Castanhal (PA). In this sense, it addresses the geographical location, the profile of women healers in the municipality of Castanhal and the know-how in the midst of urban anthropization, the elements of material and immaterial healing of the benzection and their adaptations and difficulties in healing practices. Therefore, the investigation presented the qualitative approach with descriptive-exploratory procedures and developed under an anthropic look with the methodological bias of ethnomethodology. The techniques used were: participant observation, informal conversations, audiovisual records, field notebook and interviews with five women healers. The analysis of the data identified that the women healers are located in two different zones, four of them are located in the Area of the Compact City of Priority Occupation (ACPO) and corresponds to the respective neighborhoods: Novo Olinda (Dona Dedê), Caiçara (Dona Rosilda), Milagre (Dona Gertrudes), São José (Dona Maria) and a live in Predominantly Residential Zone (PRZ) corresponding to the Japiim Set (Dona Sabá). The profile of the healers comprises the age group between 62 and 94 years old, they are mostly widows and Catholics, born in Pará. with an average performance of 62 years in the work of benzection and who inherited the gift of benzection from mothers, fathers and / or grandparents. The process of urban anthropization is marked by industrialization, businesses and services, producing different ways of acquiring its elements of healing in the craft of benzetion, in addition to revealing anguish and yearning for them, caused by the scarcity of such elements, with a close adaptation relationship, which leads the healers to carry out their practices with the elements cultivated in their own backyards in the face of continuous urban growth. It was found that they are organized in micro-territories that structure an urban network of reciprocity and solidarity, which promotes exchanges of values and interpersonal dialogue. The healers women of Castanhal treat their gift as an intrinsic and legitimate element and as a gift from the divine. So their practices present genuinely Amazonian craftsmanship anthropization that will survive in the face of the interrelationship of the urban and continuous growth of the city. The presence of benzection is configured as an act of resistance from a rural past that tenses and eases urban geographical imagery. Through their narratives, it is noticed that the action of urban anthropization on their healing trades ends up overcoming the difficulties with adapting to new elements in their practices. The appreciation and recognition of the work of women healers in Castanhal is a necessary action to value and maintain the blessing and the blessing in the municipality, in addition to being a powerful instrument to face the dehumanization crisis.